ANALISIS KEMAMPUAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) KURIKULUM 2013 - Vidiarti, Erni; Zulhaini, Zulhaini; Andrizal, Andrizal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This research aims to analyze the ability of Islamic religious education teachers in the preparation of the plan of implementation of the learning (RPP) Curriculum 2013 in SD Negeri 016 Source Flat Singingi Subdistrict. This research includes research with qualitative, descriptive approach to research that is used to describe and analyze the phenomena, events, social activities, attitudes, beliefs, perceptions, and people individually and the group, with the techniques of data collection through the techniques of observation, interview and documentation. Results of the study showed that the ability of guru PAI in the preparation of RPP 2013 in elementary curriculum Land Resource 016 Flat Sub Singingi categorized